URB2 as an important marker for glioma prognosis and immunotherapy - Fang, Chaoyou; Zhang, Zeyu; Han, Yongquan; Xu, Houshi; Zhu, Zhengyang; Du, Yichao; Hou, Pinpin; Yuan, Ling; Shao, Anwen; Zhang, Anke; Lou, Meiqing (Frontiers in Pharmacology, 2023)
URB2 ribosome biogenesis homolog (URB2) is localized in the nucleolus and is essential for ribosome biogenesis. To date, no research has addressed the specific roles of URB2 in tumorigenesis and progression. Therefore, we investigated the predictive value of URB2 in glioma and elucidated its relationship with immunity in this study. The clinical data were acquired from the Chinese Glioma Genome Atlas (CGGA) database and validated by the Gene Expression Omnibus (GEO) database, The Cancer Genome Atlas (TCGA) dataset, Clinical Proteomic Tumor Analysis Consortium (CPTAP) database, and Western blot (WB) analysis. By Cox regression analyses, we examined the association between different variables and overall survival (OS) and its potential as an independent prognostic factor. Then, we used Gene Set Enrichment Analysis (GSEA) to confirm significant biological pathways related to URB2. By constructing a nomogram that incorporates both clinicopathological variables and the expression of URB2, we provide a model for the prediction of prognosis. Moreover, we explored the relationship between immunity and URB2 and elucidated its underlying mechanism of action. We revealed that URB2 is unrelated to TMB in LGG (p = 0.0075). Several tumor-infiltrating lymphocytes and immune checkpoints correlated with URB2 were found. Furthermore, a significant correlation between URB2 and the immune-suppressive microenvironment for glioblastoma (GBM) was demonstrated by the Timer Database and ESTIMATE. In conclusion, our research suggested that URB2 is likely to play an oncogenic role in gliomas and revealed a close relationship between immunity and URB2, which suggests a new approach to immunotherapy for glioma.